Natalizumab restores aberrant miRNA expression profile in multiple sclerosis and reveals a critical role for miR‐20b. (5th December 2014) - Ingwersen, Jens; Menge, Til; Wingerath, Britta; Kaya, Derya; Graf, Jonas; Prozorovski, Tim; Keller, Andreas; Backes, Christina; Beier, Markus; Scheffler, Matthias; Dehmel, Thomas; Kieseier, Bernd C.; et al.
Abstract Objective To identify microRNAs (miRNAs) regulated by anti‐α4 integrin monoclonal antibody therapy (natalizumab) in the peripheral blood of patients with relapsing‐remitting (RR) multiple sclerosis (MS) and to confirm their role in experimental settings in vivo. Methods In a longitudinal study of 17 RR‐MS patients, we investigated blood miRNA expression profiles at baseline and after 1 year of natalizumab therapy by microarray technique and quantitative PCR validation. We compared the baseline expression profiles of these patients to those of 18 age‐ and sex‐matched healthy controls. We confirmed the contribution of resulting candidate miRNAs in an animal model of MS, experimental autoimmune encephalomyelitis (EAE) induced by adoptive transfer of proteolipid protein (PLP)139–151‐activated lymphocytes in SJL/J mice or by active immunization of miR‐106a 363‐deficient C57BL/6 mice (or wildtype litter mates) with myelin oligodendrocyte glycoprotein (MOG)35–55. Results Our longitudinal analysis revealed that miR‐18a, miR‐20b, miR‐29a, and miR‐103 were upregulated and predominantly expressed by CD4+ T cells, whereas miR‐326 was downregulated upon natalizumab treatment. A comparison of untreated RR‐MS patients at baseline with healthy controls revealed that the four natalizumab‐upregulated targets were initially downregulated in MS. All confirmed targets showed disease‐dependent expression in splenocytes of mice suffering from EAE. Genetic deletion of the miRNA cluster miR‐106a 363 (containing natalizumab‐regulated miR‐20b) resulted in a more severe EAE course and an in vivo upregulation of the miR‐20b target genes rorgt, stat3, and vegfa. Interpretation Our study indicates that natalizumab restores dysregulated miRNA patterns in MS and reveals the contribution of miR‐20b in autoimmune demyelination in vivo.